Exploring the Impact of Patriotism, Volunteerism and Perceived Empowerment on Community Engagement in Sports Events - Azzura Nordin; Aziz Jamal; Nor Zaihan Hasan Mat Hussin; Mohd Zulkifli Abdullah; Saadiah Juliana Saadun (Information Management and Business Review, 2023)
This paper examines the role of patriotism, volunteerism, and perceived empowerment in fostering community engagement during sports events. Using purposive sampling, this study employed 174 undergraduate event management students to answer questionnaires that measured patriotism, volunteerism, perceived empowerment, and community engagement. The relationship of studied variables was primarily analyzed using correlational and multivariate regression analyses through structural equation modeling (SEM). The results of the analyses identified patriotism, voluntarism, and perceived empowerment statistically and significantly influenced respondents` community engagement. Patriotism also emerged as a predictor that influenced community engagement the most. The findings underscore the importance of understanding the specific event context in shaping the influence of these factors. The study highlights the significance of community engagement in sports events for sports management research and practice, emphasizing the motives behind voluntary participation and the potential impact on community development and social outcomes